Effect of tempering on thermal analysis of Al-Ti-Si alloy and its composites - Anaee, Rana Afif (Iraqi Journal of Physics, 2019)
The investigation of the effect of tempering on thermal analysis of Al-Ti-Si alloy and its composites with MgO and SiC particles was performed. Thermal analysis was performed before and after tempering by DSC scan. Optical microscopy was used to identify the phases and precipitations that may be formed in base alloy and composites. X-ray diffraction test indicated that the Al3Ti is the main phase in Al-Ti-Si alloy in addition to form Al5Ti7Si12 phase. Some chemical reactions can be occurred between reinforcements and matrix such as MgO.Al2O3 in Al-Ti/MgO, and Al4C3 and Al(OH)3 in Al-Ti/SiC composite. X-ray florescence technique is used to investigate the chemical composition of the fabricated specimens. Heat treatment (Tempering) changes the microstructure of base alloy and its composites which was assessed by DSC scan. Generally, three main peaks appeared in DSC represented by GP zone, S phase (precipitations) and dissolution of phases or precipitations. After tempering, composite with SiC particles showed better results than base alloy and composite with MgO. Since the optical microscopy revealed reforming the stable phase Al3Ti with evaporation some gases from composite. DSC analysis showed the stability of composite with SiC was up to 270oC.